The relationship between marketing agility and financial performance under different levels of market turbulence - Zhou, Jing; Mavondo, Felix T.; Saunders, Stephen Graham (Industrial marketing management, 2019)
Marketing agility is an example of dynamic capability that has significant influence on ordinary capabilities leading to superior financial performance. This makes it of interest to marketing managers. Yet the way in which this capability aligns with turbulent market environments to simultaneously influence ordinary capabilities and performance has not been adequately examined and empirically tested. This study seeks to close this gap by positing that marketing agility has both direct and indirect (through innovation capability which is an ordinary capability) impacts on financial performance. However, these relationships are moderated by market turbulence to yield both mediated moderation and moderated mediation effects. The study was undertaken in the Chinese food-processing industry where a sample of 518 companies participated. This provides an opportunity to validate theory developed in the western economies and to generalize some previous findings. Contrary to received literature we found that the impact of innovation capability on financial performance is stronger under low market turbulence; and that market turbulence moderates the indirect relationship between marketing agility and financial performance. The indirect effect is stronger when market turbulence is low than when it is high. Implications for managers and academia are discussed and limitations of the study are pointed out. •Marketing agility, one example of a dynamic capability both directly and indirectly influences financial performance.•Market turbulence moderates the indirect effect of marketing agility on financial performance such that the indirect effect is stronger when market turbulence is low.•he development and deployment of dynamic capabilities is most beneficial under low to moderate market turbulence.